La poétique du paysage chez Derek Walcott - Dominique Aurélia (VertigO)
This paper proposes to explore some specific aspects of imagery in Derek Walcott’s poetry, with special reference to the notions of landscape and memory. Walcott’s linguistic heritage as a StLucian prompts him to develop a heterophonic poetics which in his interrogation on blank spaces voids and amnesia creates ambiguity and irony.